Bigger is better: changes in body size explain a maternal effect of food on offspring disease resistance. Issue 5 (3rd February 2017) - Garbutt, Jennie S.; Little, Tom J.
Abstract: Maternal effects triggered by changes in the environment (e.g., nutrition or crowding) can influence the outcome of offspring–parasite interactions, with fitness consequences for the host and parasite. Outside of the classic example of antibody transfer in vertebrates, proximate mechanisms have been little studied, and thus, the adaptive significance of maternal effects on infection is not well resolved. We sought to determine why food‐stressed mothers give birth to offspring that show a low rate of infection when the crustacean Daphnia magna is exposed to an orally infective bacterial pathogen. These more‐resistant offspring are also larger at birth and feed at a lower rate. Thus, reduced disease resistance could result from slow‐feeding offspring ingesting fewer bacterial spores or because their larger size allows for greater immune investment. To distinguish between these theories, we performed an experiment in which we measured body size, feeding rate, and susceptibility, and were able to show that body size is the primary mechanism causing altered susceptibility: Larger Daphnia were less likely to become infected. Contrary to our predictions, there was also a trend that fast‐feeding Daphnia were less likely to become infected. Thus, our results explain how a maternal environmental effect can alter offspring disease resistance (though body size), and highlight the potential complexity of relationship between feeding rate and susceptibility in a host that encounters a parasite whilst feeding. Abstract : Food‐stressed Daphnia give birth to offspring that are larger, feed at a lower rate, and show a low rate of infection when exposed to an orally infective bacterial pathogen. This reduced disease resistance could result from slow‐feeding offspring ingesting fewer bacterial spores or because their larger size allows for greater immune investment. Our data show that the primary mechanism causing altered susceptibility was body size, with feeding rate being less important.